Marketing Agility and Innovation: Boosting Performance in the Used Car Market - Anah Furyanah; Iis Noviyanti; Fauziah Septiani (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: Marketing agility has become a critical capability within firms classified as small and medium-sized enterprises (SMEs) to sustain marketing performance within increasingly dynamic and competitive markets. Within the context of Indonesia’s pre-owned car industry, the present research examines the intervening role of marketing innovation in explaining how marketing agility influences marketing performance.Methodology: A quantitative approach was employed using survey data collected from 289 used car SMEs operating in the Jabodetabek region. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the data, with the model specified at both the first-order and second-order levels.Findings: The empirical results reveal that marketing agility exerts a significant positive influence on both marketing innovation and marketing performance. In addition, the findings indicate that marketing innovation partially mediates the relationship between marketing agility and marketing performance, suggesting that marketing agility influences performance both directly and indirectly through marketing innovation. At the dimensional level, proactiveness, responsiveness, and speed exhibit significant indirect effects on marketing performance through marketing innovation, whereas flexibility does not demonstrate a significant effect. Moreover, market turbulence is found not to moderate the relationships among marketing agility, marketing innovation, and marketing performance.Conclusion: The results emphasize the crucial role of marketing agility and marketing innovation in enhancing marketing performance under relatively stable market conditions.